Leaf Micromorphological Studies in Subfamily Bambusoideae and Pooideae from Gujarat, India - Desai, Rinku J.; Raole, Vinay M. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Leaf is the most widely used vegetative organ for identification in plant taxonomy. Microscopic features such as epidermal cells, stomata, cuticle, surface contours, roughness and ornamentation are in use since the beginning of the last century. Information on foliar micromorphology can shed more light on structural features and their possible functional attributes. In the present study 14 species belongs 4 tribes has been studied from the vegetative characteristic features of the leaves. All the species has been studied for their variations at generic level and tried to utilize for preparation of artificial key. All the characters has been discussed at length and presented in a tabular form.